The Performance of Inorganic Passive Fire Protections: an Experimental and Modelling Study - A. Tugnoli; G. Landucci; V. Villa; F. Argenti; V. Cozzani (Chemical Engineering Transactions, 2013)
The installation of fireproofing materials on equipment and structures is a widely applied and effective solution for the protection of critical process elements against severe fires, in order to prevent possible damages escalation. The choice and design of fireproofing materials is crucial for granting adequate performances. As a matter of fact, properties such as, among others, thermal conductivity and density change substantially when the material is exposed to severe temperatures. In the present study, a methodological approach, integrating experimental and modelling activities, was proposed. Focus was set on a particular class of PFP: inorganic fireproofing materials. A reference set of commercial PFP materials (rock wool, glass wool, silica blanket, etc.) was selected. Small scale experiments allowed determining the variation of the most relevant thermal properties of the coatings and to obtain detailed correlation models for their description. A finite element model (FEM) was developed in order to reproduce the behaviour of real scale equipment exposed to fire and to provide a sound design of the fire protection system.